Inhaled Nitric Oxide and Cerebral Malaria: Basis of a Strategy for Buying Time for Pharmacotherapy - Bergmark, Brian; Bergmark, Regan; Beaudrap, Pierre De; Boum, Yap; Mwanga-Amumpaire, Juliet; Carroll, Ryan; Zapol, Warren (The Pediatric Infectious Disease Journal, 2012)
There are approximately 225–600 million new malaria infections worldwide annually, with severe and cerebral malaria representing major causes of death internationally. The role of nitric oxide (NO) in the host response in cerebral malaria continues to be elucidated, with numerous known functions relating to the cytokine, endovascular and cellular responses to infection with Plasmodium falciparum. Evidence from diverse modes of inquiry suggests NO to be critical in modulating the immune response and promoting survival in patients with cerebral malaria. This line of investigation has culminated in the approval of 2 phase II randomized prospective clinical trials in Uganda studying the use of inhaled NO as adjuvant therapy in children with severe malaria. The strategy underlying both trials is to use the sytemic antiinflammatory properties of inhaled NO to “buy time” for chemical antiparasite therapy to lower the parasite load. This article reviews the nexus of malaria and NO biology with a primary focus on cerebral malaria in humans.
Keywords: Inhaled nitric oxide; Cerebral malaria; Nitric oxide synthase; Plasmodium falciparum